Childhood cancer in Italy: background, goals, and achievements of the Italian Paediatric Hematology Oncology Association (AIEOP). Issue 5 (October 2021) - Zecca, Marco; Ferrari, Andrea; Quarello, Paola; Rabusin, Marco; Balduzzi, Adriana; Buldini, Barbara; Rostagno, Elena; Prete, Arcangelo; Favre, Claudio; Massimino, Maura; Biondi, Andrea; Porta, Fulvio; et al.
This article reviews the primary goals and achievements of the Italian Association for Pediatric Hematology-Oncology (Associazione Italiana Ematologia Oncologia Pediatrica [AIEOP]), a national cooperative group that has been working for children and adolescents with cancer in Italy since 1975.